Exportaç\~oes e processos inovativos: Um estudo para a América Latina e a Europa do leste - Marcelo José Braga Nonnenberg; Ana Paula Avellar (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– In the last decades one of the main engines of foreign trade growth has been innovation, the process of embedding knowledge in production processes. The purpose of this paper is to supply evidence favoring the hypothesis that innovation contributes positively to export performance when we control for endogeneity and selection bias by means of instrumental variables and Heckman selection model. The analysis is based upon a sample of firms from the Enterprise Surveys by the World Bank for Latin America and Eastern Europe. Evidence support the existence of a behavior pattern among firms in both regions. Size, age and foreign capital share have a positive influence on export decision. There is also a positive relationship between innovation and the likelihood of firms becoming exporters. Based on Heckman procedure, we also find evidence that innovative firms are more likely to become exporters but once they become exporters, the export intensity (relative to sales) affect negatively the result, only to Latin America countries.
Keywords: F14; O30; 330; exports; innovation; Latin America; East Europe; selection bias